Réponses

  • Omnes
  • Modérateur confirmé
2014-03-03T23:42:10+01:00
Salut,

(2t - 1)² <(-t + 1)(-2t + 1) 

(2t-1)² - (-t+1)(-2t+1) < 0
(2t-1)(2t-1) -
(-t+1)(-2t+1) < 0
(2t-1)[(2t-1) - (-t+1)] < 0
(2t-1)(2t-1 +t - 1) < 0
(2t-1)(3t -2) < 0
2t - 1 < 0
2t < 1
t < 1/2
3t - 2 < 0
3t < 2
t < 2/3

S = ]-infini; 1/2[

 3/(2a) ≥ -4/(a-1)


 \frac{3}{2a}   \geq  \frac{-4}{a-1}\\&#10; \frac{3}{2a} - \frac{-4}{a-1}  \geq 0\\&#10; \frac{3(a-1)}{2a(a-1)} -  \frac{-4(2a)}{2a(a-1)}   \geq 0\\&#10; \frac{3(a-1) - (-4(2a))}{2a(a-1)}  \geq 0\\&#10; \frac{3a - 3 + 8a}{2a(a-1)}   \geq  0\\&#10; \frac{11a - 3}{2a(a-1)}   \geq  0

11a - 3 ≥ 0
11a ≥ 3
a ≥ 3/11

et
2a(a-1) ≠ 0
2a ≠ 0
a ≠0
a - 1 ≠ 0
a ≠ 1
S = [3/11; 1[ U ]1; + infini[

Bonne soirée !



Comment on met en facteur commun la première parce que (2t-1) ce b'est pas comme (-2t+1) ?